The site mapping of Kakucs-Turján by the means of horizontal and vertical proxies: Combining field and basic laboratory methods of geoarchaeology and archaeological prospection - Peto, Akos; Niebieszczański, Jakub; Serlegi, Gabor; Jaeger, Mateusz; Kulcsar, Gabriella (My University, 2019)
The homogenous cultural identity that emerged during the Middle Bronze Age (2000–1450 cal BC) in the central territory of the Carpathian Basin is identified uniformly as the Vatya culture. The Vatya people created multilayered tells, open air horizontal, as well as fortified settlements along the western and eastern bank of the Danube river. These archaeological sites are significant elements of both the cultural and natural heritage of the Carpathian Basin. Their significance does not only lie within the possibility to reconstruct the life, society and material culture of Vatya populations, but the buried soils and anthropogenic sediments hold significant information on prehistoric human-environment interactions, and on site formation processes that occurred after the abandonment of the individual settlements. Geophysical prospection methods and field walking helped to locate and identify the tripartite structure of Kakucs-Turján archaeological site within the territory of the Danube–Tisza Interfluve. The settlement was established on the border of different geographical micro-regions and at the conjunction of dissimilar natural geographical environments. The stratigraphy of the site was described by the means of high resolution and focused series of hand auger observations, as well as on the basis of basic soil physical and chemical parameters. The detailed macro-morphological description of the soil core profiles aimed at precisely identifying the soilscape of the site and its vicinity, the stratigraphy of the anthropogenic and natural sediments of the settlement, but also to facilitate our understanding of the site formation process. Data gained by the means of geoarchaeological methods not only form the basis of environmental historical conclusions, but reveals mosaics of the interaction between ancient human populations and their environment. 1. Introduction 1.1. Archaeological background One of the most distinctive traits of the Middle Bronze Age (MBA; ca. 2000–1450 cal BC) in the central basin of the Danube (and in a broader context across the entire Carpathian Basin) was the dynamic development of fortified settlements (Earle and Kristiansen, 2010; Jaeger, 2016). Some of the settlements functioned uninterruptedly for a number of centuries; as a result, the current thickness of cultural layers ranges from several to over 10 m (...)
Keywords: bronze age; stratigraphy; geoarchaeology; fortified settlement